2019
DOI: 10.4314/ahs.v19i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Targeted screening for primary immunodeficiency disorders in the neonatal period and early infancy

Abstract: Background Primary immunodeficiency diseases (PID) comprise a group of more than 300 diseases that affect development and /or function of the immune system. Objectives The aim of this study was diagnosis of PID among a suspected group of neonates and infants within the first six months of life as well as identifying the warning signs of PID characteristic to this period. Method Fifty neonates presenting with warning signs of PID were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
(48 reference statements)
2
10
0
Order By: Relevance
“…Our diagnostic yield (34.72%, 25/72) was similar to that observed in European 21 and Egyptian patients. 22 In a recent systematic review, Yska et al 23 reported that the diagnostic yield of NGS in mixed PID groups ranged from 15% to 46% (median = 25%), which is consistent with that derived from our cohort. When we inspected the associated clinical signs 24 among patients with PID from NICUs, we found that severe infections were the most common presentations, followed by atopic dermatitis and protracted diarrhoea.…”
Section: Discussionsupporting
confidence: 89%
“…Our diagnostic yield (34.72%, 25/72) was similar to that observed in European 21 and Egyptian patients. 22 In a recent systematic review, Yska et al 23 reported that the diagnostic yield of NGS in mixed PID groups ranged from 15% to 46% (median = 25%), which is consistent with that derived from our cohort. When we inspected the associated clinical signs 24 among patients with PID from NICUs, we found that severe infections were the most common presentations, followed by atopic dermatitis and protracted diarrhoea.…”
Section: Discussionsupporting
confidence: 89%
“…[11,12] However, the studies in some PID centers also established the prevalence of CID among the cases. [2,13,14] Not all PID groups are represented in our regional PID registry. Defects in intrinsic and innate immunity, autoinflammatory disorders, and complement deficiencies were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, these signs are very important for PID diagnostics in the neonatal period and early infancy. [14] Since there is currently no neonatal screening for PIDs in Ukraine, defining of these symptoms is very important for a timely diagnosis of these diseases. [18] This study was limited to pool of patients followed up in one regional center.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the prevalence of PIDs in Egypt is lacking as there is no national registry to date. The ESID database contains data from Egypt and some information can also be gained from the few published studies (33,(45)(46)(47). CID is considered the most common disease (31%), followed by predominantly antibody deficiency (30%), welldefined syndromes with PID (17.5%), and, finally, phagocytic defects (8.1%).…”
Section: Status In Egyptmentioning
confidence: 99%